Ensino de Programação e Algoritmos na educação profissional técnica de nível médio: uma revisão sistemática da literatura - Marques, Erik do Carmo (2024)
Brazil’s Law No. 9,394/1996, which outlines the guidelines and foundations of national education, also governs technical and vocational education at the secondary level. This law emphasizes the comprehensive development of students, preparing them for professional activities. According to the National Education Plan (PNE, 2014), by 2024, enrollments in this educational modality are expected to triple, with at least 50% of this growth occurring in public education. This expansion demands that educational institutions, administrators, and teachers pay special attention to maintaining teaching quality and addressing the inherent challenges. In Information and Communication Technology (ICT) courses, both at the secondary and higher education levels, a key challenge is ensuring student learning, motivation, and engagement in introductory programming courses. In this context, the present study aims to summarize, categorize, and discuss primary studies on the teaching of algorithms and programming in ICT courses within Brazil’s vocational education system from 2014 to 2023, through a systematic review. Utilizing databases such as Peri´odico CAPES and SCOPUS, an initial selection of 2,994 articles was made through search strings, with 2,967 being excluded during two review phases, leaving 27 primary studies. The main findings indicate that Java is the most commonly used programming language, Arduino is the most frequent platform, and game creation is the most widely adopted learning strategy. Additionally, the studies predominantly focused on integrated technical education, primarily within technical computer science courses. The most commonly identified challenge was students’ difficulty with logical-mathematical reasoning, akin to issues observed in higher education studies.